The Africanization of the Methodist Church : with special focus on the Revs. Zaccheus R. Mahabane and the Rev. Seth Mokitimi - Mchlauli, Henry (Department of Religious Studies, 2023)
This thesis discusses two African church leaders, the Rev. Zaccheus R. Mahabane and the Rev. Seth Molefi Mokitimi, and the role they played in eliciting change in the Methodist Church of Southern Africa. The thesis observes that social, political and economic factors influenced change in the Methodist Church of Southern Africa (MCSA). The role played by black leaders was important in moving the church out of its past to become a voice for the voiceless. Though Mahabane's and Mokitimi's social locations were different, the causes to which they gave their full measure of devotion were comparable. They both served the church in different ways and at times in similar committees where they strove for the realization of African tradition and customs within the church. They challenged the Church in their own way to consider the African cultures and tradition. The study of both theologians clearly demonstrates that they did in their own way contribute towards the Africanization of the church although they were deeply anchored in a church tradition. Each of them developed a theological ethic towards this end This thesis further argues that both leaders attempted to challenge the church towards indigenization and Africanization, incorporating African values into the life of the church and addressing the question of how these can contribute new facets to the church. Issues such as polygamy, African rites, lobola and circumcision are now on the Methodist agenda. An investigating committee on the question of the impact of African customs on the Church has been instituted. Both Mahabane and Mokitimi played a pertinent role in the recognition of African customs and culture by the Methodist Church, which has happened only since 1960. The emergence of a highly articulate and purposeful contribution from black clergy, the subsequent election of a black President of Conference, the appointment of a Commission on Africanization and the role of the Manyanos all tell of a Methodist Church that strives to be of Africa. The Commission on Africanization has been tasked with defining the concept of Africanization in relation to the function of the church in respect of liturgy and form of worship. Both Mahabane and Mokitimi ensured that the traditional beliefs would find their fullest expression in the church, and thus assured that the MCSA affirmed its African roots. The Obedience Conference of 1981, the most representative assembly in 165 years of the history of the MCSA, was a clear commitment to Africa. The conference affirmed that the MCSA is a Church in Africa, and it is vital that the riches of Africa be appropriated into the church worship, music and liturgies. The institution of the commission on Africanization suggests that the Methodist Church is committed to enforcing Africanization and indigenization in the church. The call for a 'Journry to a Ne:v Land" is another aspect which demonstrates that the Methodist Church is willing and committed to shaping the mindset of its members. This thesis further observes that the Black Methodist Consultation (BMC) and Manyano's in the Methodist Church served as important Africanizing mechanisms in the church. They have never given in to western influences but have striven to maintain their own values. The contribution of the Manyano's in the times of the struggle was essential. The Manyano's were successful in empowering black people in the church, especially women. The role they played was that of shaking off the shackles of colonialism by changing the mindset of the people for the realization of an African identity. Their all-night revival meetings, African style singing, dancing and movement, exposition of the Word by human laity, healing and exorcism, etc are important African experiences that the Manyano's made use of. The thesis further offers a critical analysis on the BMC and argues that it is no longer relevant given its exclusivity in nature. The author proposes an alternative structure or a restructuring of the BMC to become an inclusive structure that will speed up the move towards the Africanization of the church. The thesis further offers a comparative analysis between the leaders under investigation and notes that both leaders espoused an interpretive framework for analyzing the South African situation. They both discussed similar concepts such as reconciliation, the role of the church and social change, and were committed in their own way of the welfare of South Africa. However, they differed in their political agenda. Mahabane appeared more radical than Mokitimi. The thesis notes that Mokitimi's uncritical political praxis is a microcosm of the kind of theology perpetuated by the Methodist Church. The process of indigenization and Africanization has become a common denominator for transformation in the church. This thesis notes that the level at which churches themselves have attempted to grapple with this remains to be answered. It appears that some churches are not concerned about the realization of this transformation. The debate and realization of it is only cantered among theologians of the mainline churches, such as the English-speaking churches. The questions is, is there any impetus to "ring the bells" for Pentecostal theologians and those of other charismatic churches or to what extent are the theological seminaries and Biblical Correspondence Colleges contributing to this? This thesis submits that even though the debate on indigenization and Africanization is dominated by Christian theologians, it should rather not be regarded as a Christian endeavour only. All theologians irrespective of their religion should engage in this realization. To commit oneself to it is to search for a greater unity of the religions practised in Africa. This realization expressed in language, worship etc holds us all together, and to recognize it is to come to terms with Africa, shaking off European dominance This thesis shows that the Methodist Church has committed itself to this debate but, even so, there are those members who remain sceptical of the process. The only remedy is for the Church to transform their attitude. There is a need to conscientize ministers around the process of the indigenization and Africanization of the Church, so that they will help in shaping the mindset of the people. For the realization of this, all Methodists must join in making it happen.